Kritik Ilmu Ekonomi Strukturalis dan Islam Terhadap Ekonomi Klasikal - Handi Risza (Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 2014)
The Critics of Structuralis Economics and Islam To Neo-Clasical Economy. This reserach proves that in the Islamic economic thought and structuralist discourse, the idea of economic and social transform is very strong, in the mean time, there is a lot of criticisms and corrections towards neoclassical economic thought. The idea of transformation is needed to re- establish economic credos and thoughts that put forward moral values and humanitarian system of ethics in the quest of economic justice and prosperity. The conclusion of this paper supports that there is an urgent need of social and economic transformation in order to establish social justice and economic prosperity. The conclusion is also a refutation to the views developed by neoclassical economic thinkers, who based their views on individual interest and free competition to realize prosperity and justice for the society.  DOI:10.15408/aiq.v6i2.1234